ChemInform Abstract: Enantioselective Deprotonative Ring Contraction of N1‐Methyl‐N4‐Boc‐benzo[e][1, 4]diazepine‐2, 5‐diones. Issue 13 (March 2015) - Antolak, Stephanie A.; Yao, Zhong‐Ke; Richoux, Gary M.; Slebodnick, Carla; Carlier, Paul R.
Abstract Upon deprotonation, title compounds (I) undergo ring contraction to the corresponding quinolone‐2, 4‐diones (II) with high enantioselectivity.